The injectable hydrogel loading cannabidiol to regulate macrophage polarization in vitro for the treatment of chronic enteritis - Ye Wang; Xingming Ji; Xinyi Wang; Mengyu Sun; Cheng Li; Dongmei Wu (Journal of Applied Biomaterials & Functional Materials)
Objective: Chronic bowel disease has the characteristics of high recurrence rate, prolonged and non-healing, and the incidence has increased year by year in recent years. Cannabidiol (CBD) has significant anti-inflammatory and antioxidant activities, but it is limited by its characteristics of fat solubility and low bioavailability. This study aims to treat chronic inflammatory bowel disease by preparing a CBD-loaded hydrogel system (GelMA + CBD) that can deliver CBD in situ and improve its bioavailability through slow release. Method: The study designed and constructed GelMA + CBD, and its surface morphology was observed by scanning electron microscopy, and its pore size, swelling rate and release rate were evaluated to evaluate its bioactivity and biosafety. The expression of various inflammatory factors was detected by ELISA, and the expression of protein and reactive oxygen species were observed by laser confocal microscopy to evaluate their anti-inflammatory and antioxidant properties. Results: Our study found that GelMA + CBD with biosafety, could make CBD be slowly released, and effectively inhibit the M1-type polarization of macrophages in vitro, and promote the M2-type polarization. In addition, GelMA + CBD can also reduce the expression of pro-inflammatory factors (such as iNOS) in macrophages, and increase the expression of anti-inflammatory factors (such as Arg-1), clear intracellular reactive oxygen species (ROS), and relieve oxidative stress. Conclusion: The vitro experiments have confirmed that the CBD-loaded hydrogel system has good biosafety, and can alleviate inflammation by regulating the polarization direction of macrophages, and then inhibiting the secretion of pro-inflammatory factors, laying a strong foundation for the treatment of chronic enteritis.